A Pilot Study Of Heat Stress Risk Evaluation While Wearing Personal Protective Equipment Suit In A Tropical Climate - Ahmad Khaizi, Aini Syazwina (Universiti Sains Malaysia, 2022)
PPE is made of an impermeable material that healthcare workers put on to protect themselves from the transmission of viruses, particularly during pandemics such as SARS-CoV-2 or COVID-19. It can be a significant contributor to heat stress since the insulating effect of the clothing is essential for maintaining thermal comfort. The climate in Malaysia is hot and humid, and the average annual temperature can reach up to 25.4°C. As a result, it will cause heat stress to occur more quickly. The objective was to assess the level of heat stress when wearing PPE in a tropical climate using PSI. Two males participated in this pilot study, in which their body temperature and heart rate were measured while they engaged in activities while wearing PPE. The activities comprised standing, walking on a treadmill at a speed of 0.5 m/s and writing on a computer, walking on a treadmill at a speed of 1.5 m/s, and walking slowly around the court. These activities were included in three different studies; control and intervention in indoor and outdoor working conditions. The participants' maximum body temperature was measured at 37.8°C, their heart rates ranged from 150 to 160 beats per minute, and they experienced moderate level of heat stress while carrying out work of moderate intensity exercises. Future research must analyse the physiological responses when PPE is worn in a tropical climate using a climatic chamber and precise equipment.